PENGEMBANGAN LKPD BERBASIS AUGMENTED REALITY SEBAGAI MEDIA PEMBELAJARAN IPAS UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS KELAS IV SEKOLAH DASAR - Kurnia Sari, Gisela; Fathurrahman, Moh. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is based on the importance of technology-based learning media innovation in the 21st Century era which can improve students' critical thinking abilities. This research aims to develop Student Worksheets (LKPD) as a science learning medium based on Augmented Reality material on the Heritage of Hindu, Buddhist and Islamic Kingdoms in Indonesia for fourth grade elementary school students. In its implementation, this research uses a Research and Development approach by referring to the steps of the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The research results show that Augmented Reality-based LKPD material on the Heritage of Hindu, Buddhist and Islamic Kingdoms in Indonesia has